1996
DOI: 10.1046/j.1471-4159.1996.67010229.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Regulation of Secretory Granule‐Associated Proteins in Rat Intermediate Pituitary

Abstract: The biosynthesis of peptides requires the synthesis of the prohormone, several biosynthetic processing enzymes, and other granule constituents. We have investigated the regulated expression of proopiomelanocortin (POMC) and five enzymes essential for the processing of POMC to smaller, bloactive peptides in intermediate pituitary melanotropes. Rats were treated with a dopaminergic agonist (bromocriptine) or antagonist (haloperidol) for periods ranging from 1 h to 5 days, followed by analyses of mRNA levels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…Together, these findings may indicate that, in resting conditions, pituitary cells synthesize PAM at a rate that exceeds the needs of the cell, and therefore, its steady state is regulated by degradation. A study from our laboratory established that long term stimulation of exocytosis results in up-regulation of mRNA and protein the levels of pro-hormone and processing enzymes (36). Our present results suggest the interesting possibility that sustained exocytotic stimulation (like the one produced by the Ba 2ϩ /PMA paradigm) might regulate PAM protein levels post-translationally diverting newly synthesized enzyme molecules from a degradative pathway.…”
Section: Discussionmentioning
confidence: 53%
“…Together, these findings may indicate that, in resting conditions, pituitary cells synthesize PAM at a rate that exceeds the needs of the cell, and therefore, its steady state is regulated by degradation. A study from our laboratory established that long term stimulation of exocytosis results in up-regulation of mRNA and protein the levels of pro-hormone and processing enzymes (36). Our present results suggest the interesting possibility that sustained exocytotic stimulation (like the one produced by the Ba 2ϩ /PMA paradigm) might regulate PAM protein levels post-translationally diverting newly synthesized enzyme molecules from a degradative pathway.…”
Section: Discussionmentioning
confidence: 53%
“…To confirm the role of dopaminergic pathways in the control of intermediate lobe ACTH release, 7B2 null and WT mice received daily injections of bromocriptine, a dopaminergic agonist (34). The levels of circulating ACTH in each of the two 7B2 nulls were reduced by 46 and 51%, respectively, after one injection, and by 75 and 60% after three injections; levels of ACTH in the WT controls did not decrease.…”
Section: In Situ Hybridization Of Pomc Mrna Indicates That Pomc Produmentioning
confidence: 99%
“…Since peptide amidation is a rate limiting step in the biosynthesis of NPY and many other neuropeptides, we monitored peptidylglycine ␣ -amidating monooxygenase (PAM), the only enzyme that catalyzes this modification (Prigge et al 2000). POMC biosynthesis in melanotropes responds to dopaminergic drugs, and changes in PAM parallel POMC (Oyarce et al 1996). Earlier studies demonstrated changes in PAM and prohormone convertase 2 mRNA levels in response to acute ECS (Bhat et al 1993).…”
mentioning
confidence: 99%